Accelerating oxygen evolution electrocatalysis of two-dimensional NiFe layered double hydroxide nanosheets via space-confined amorphization. Issue 40 (9th October 2019) - Jiao, Shilong; Yao, Zhaoyu; Li, Mengfan; Mu, Ce; Liang, Huawei; Zeng, Yu-Jia; Huang, Hongwen
Abstract : Boosting OER activity of the ultrathin 2D NiFe-LDH nanosheets via the introduction of space-confined amorphism that induces the increased active sites and optimized electronic structure. Abstract : NiFe layered double hydroxides (LDHs) have received widespread attention due to their unique structures and inherent electrocatalytic activity towards the oxygen evolution reaction (OER). Extensive studies have been reported to further improve the electrocatalytic activity of NiFe-LDHs via various strategies. However, controlling the degree of amorphization and stabilizing the amorphous zone during the electrocatalytic process are still challenging. Here, we report a facile method to synthesize a space-confined amorphous NiFe-LDH (SCA-NiFe-LDH) by selectively etching the surfaces of electrocatalysts. Due to the successful anchoring of amorphous zones onto the basal planes of the two-dimensional NiFe-LDH, the optimized SCA-NiFe-LDH exhibits high electrocatalytic activity with a low overpotential of 190 mV at 10 mA cm −2, a Tafel slope of 31 mV dec −1 and excellent long-term stability. The substantially enhanced OER performance is attributed to the increased amount of active sites and the modified electronic structure of NiFe-LDH after amorphization.